Pengaruh Stratifikasi Sosial Terhadap Kesadaran Hukum Kajian Empirik pada Universitas X - Dhian Tyas Untari; Desyana Berliana; Iswiyati Kunti; Fadilah; Tiara Yuliana Wanti; Sri Mega Susanty Viadolorosa Ninu; Mifta hul Zannah (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
Social stratification and legal awareness are topics of study, especially in the social sciences, which are very interesting to do. The paradigm that the higher the education will increse the more of law awareness, becomes a phenomenon that needs to be discussed. This study aims to; 1) analyze whether there is an effect of educational stratification on legal awareness, 2) analyze how to build legal awareness in the community. The study involved 30 respondents who were academics from University X, Bekasi. Education Straktas are classified into three; S1, S2 and S3. Indicators related to legal awareness are legal knowledge, legal understanding, legal attitudes and legal behavior. Analysis using statistical parametric. The results of the study show that education strata do not have an effect on legal awareness.